Organic control of Bemisia tabaci Genn. on Capsicum annuum with entomopathogenic fungi raw secondary metabolites - Loekas Soesanto; Bisiril Fatihah; Abdul Manan; endang Mugiastuti; Nur Prihatiningsih (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Soesanto L, Fatihah B, Manan A, Mugiastuti E, Prihaningsih N. 2020. Organic control of Bemisia tabaci Genn. on Capsicum annuum with entomopathogenic fungi raw secondary metabolites. Biodiversitas 21: xxxx. Control of whitefly with entomopathogenic fungi raw secondary metabolites and their correlation was investigated under control condition. The in vitro test used randomize completely design consisted of five treatments (raw secondary metabolites of Beauveria bassiana B16 and B10, Metarhizium anisopliae M16, Lecanicillium lecanii L16, and no treatments) and repeated five times. The in planta one used Latin square design consisted of five treatments and repeated five times. Variables observed were the mortality of whitefly imago, chitinolytic index, incubation period, viral disease intensity, plant height and total leaves per plant. The results showed that all treatment of raw secondary metabolites of entomopathogenic fungi caused mortality in the B. tabaci imago by 77.8% (B. bassiana B16); 71.5% (B. bassiana B10); 66.7% (M. anisopliae M16); and 59.5% (L. lecanii L16). All raw secondary metabolites of entomopathogenic fungi reduce the intensity of viral diseases by 79.98% (B. bassiana B16); 74.00% (B. bassiana B10); 72.23% (L. lecanii L16); and 55.41% (M. anisopliae M16). The correlation between B. tabaci mortality due to raw secondary metabolites of entomopathogenic fungi with the viral disease intensity is very close and opposite. Every 1% increase in pest mortality causes decrease in viral intensity by 1.346%.